PERANCANGAN SISTEM PENGGAJIAN KARYAWAN BERBASIS WEB PADA PT. TUNAS UTAMA KOMPUTER BANDUNG - Roni Surahman (INFOKOM (Informatika & Komputer), 2021)
This study aims to provide a solution by designing and applying an employee attendance system workflow based on an existing manual attendance and payroll system at PT. Tunas Utama Computer Bandung, which is still less effective and efficient, and computerized attendance applications with both the database system, user interface, and the user itself. The research method used is descriptive method, which is a method that only describes and summarizes various conditions, situations or various variables. The development or approach to information systems used in this Final Project uses the Waterfall development method. While the tools used in the analysis of system design are Flowmaps, context diagrams, Data Flow Diagrams & UML, while the implementation of system design is the PHP programming language and MySQL Server as a database. The creation of an employee payroll information system is integrated with an employee attendance system that can help the performance of PT Tunas Utama Computer especially in the field of HR management and financial management to be more organized, computerized and Web-based. Research results employee payroll system that is integrated with a web-based attendance system can overcome problems that often arise in the previous system. For example, data duplication, damage and data recap errors, so that the implementation of a web-based payroll system from MySQL as a place to store data or documents so that existing data will not be lost. Financial management has become more effective and efficient.